MENUJU INDONESIA PINTAR DENGAN METODE BAPAK PRESIDEN TAWAF UNTUK PENINGKATAN PRESTASI DAN MUTU PEMBELAJARAN - Edy Riyanto (Program Studi Pendidikan Agama Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2020)
Learning Innovation by the author, emphasizes simple, applicable and creative models and methods. This Learning Innovation aims to improve the achievement and quality of learning, towards Smart Indonesia. Hopefully, using the method of Mr. President Tawaf an increase in achievement and quality of learning. The Implementation of Learning Innovation, which also aims to describe the learning of science by the method of Mr. President Tawaf, is applied to students in the 2019/2020 school year. This activity begins with planning, implementation, monitoring and evaluation / reflection. The study was conducted by applying the method of Mr. President Tawaf. The object of this research is junior high school students. This research activity was carried out by implementing Mr. President Tawaf's approach to learning science. The results of this study showed that the learning achievement test was classified as good by observing the completeness of learning outcomes, a significant increase occurred. Science learning by the method of Mr. President Tawaf apparently can improve learning achievement and quality. It is recommended to apply this learning pattern, so students become accustomed to actively involved in learners